Radiological Assessment of the Morphology and Morphometry of Cervical Vertebral Transverse Foramina in the Adult Population of Benghazi, Libya - Nowara Elsharif; Seraj Alzentani; Mustafa Karwad; Kamla Mohamed; Arwi Elfseie (AlQalam Journal of Medical and Applied Sciences, 2025)
The transverse foramen (TF), located within the transverse process of the cervical vertebrae, serves as a conduit for vertebral vessels and sympathetic nerves. This study aimed to investigate natural anatomical variations of the transverse foramen within a Libyan population. A retrospective analysis was conducted on 100 Libyan patients with structurally healthy cervical vertebrae (mean age: 39.3 ± 10.2 years), randomly selected from cases that underwent three-dimensional computed tomography (CT) of the cervical spine using the GE CT 1400 system. Transverse foramina were evaluated based on their shape, diameter, and number. Data were analyzed using specialized software and the Statistical Package for the Social Sciences (SPSS), applying descriptive statistics including percentages, means, and standard deviations. The findings revealed that 83.6% of transverse foramina exhibited classical morphology. The most common anatomical variation was the presence of a double foramen resembling the number 8, observed in 7.1% of cases. Bilateral double foramina were more prevalent (64%) than unilateral ones (36%), with the highest frequency at the C6 level (39%). Additionally, 28% of transverse foramina were bilateral and located at C6. Unilateral foramina were more common on the right side (32%) than the left (14%), particularly at the C5 level. Congenital absence of the transverse foramen was noted in 6.1% of cases, exclusively at the C7 level. The left-sided foramina were generally larger in diameter than those on the right. The Libyan population demonstrates a predominance of classical transverse foramen morphology, comparable to patterns observed in populations of the Mediterranean basin. These findings underscore the importance of preoperative CT imaging and precise anatomical assessment of the cervical transverse foramina prior to surgical intervention. Further large-scale studies are recommended to validate and expand upon these results